TEACHERS’ PERCEPTIONS OF TASK-BASED LANGUAGE TEACHING IN ENGLISH CLASSROOM - Erwin Pohan; Emilia Andhini; Evi Nopitasari; Yoke Levana (Universitas Negeri Padang, 2016)
It is true that task-based language teaching (TBLT) is one of an effective language teaching approach to improve teachers and learners’ communication competence. This is in line with the educational policy of Indonesia inolved in the “Kurikulum 2013”, that is, enhencing teachers’ communication competence. But, the studies of TBLT in Indonesian context are very limited. The purpose of the study is to find out how the state junior, senior, and vocational high schools teachers in Tanjungpinang, Riau Archipelago Province know well about the TBLT in English classroom practice. In this case, the focuses are on their perceptions of (1) understandings of TBLT, (2) views of implementation TBLT, and (3) reasons to use or avoid implementing TBLT in their English classroom. This is conducted in descriptive qualitative approach. All the EFL teachers of those schools are as the research subjects (55 teachers of 23 schools). Survey method, four sections questionnaire – research instrument (adapted from Jeon and Hahn, 2006) is used to collect data. such as general and demograhic information, teachers’ understandings of TBLT, teachers’ views on implementing TBLT, and reasons of using or not using TBLT. All the teachers are asked to fill in the questionnaire. Data analysis conducted through interpretation of each items to see the quality of their perceptions and Likert-scale to see their perceptions’ quantity. The results showed that most of the teachers had good understandings and positive attitudes/views of TBLT. Classroom observation and deepen interview of these are suggested for future research.